Analisis Efisiensi Modal Kerja Terhadap Pertumbuhan Laba Pada PT. Kawasan Industri Makassar (Persero) (PT. Kima Makassar) - Chindi lainora; Sabirin Iskandar; Abdullah Abdullah (POLITEKNIK KETENAGAKERJAAN, 2023)
This study aims to determine the company's working capital has shown efficiency in increasing better profit growth. The author's research object is PT. Makassar Industrial Estate (Persero). This research method is descriptive research using quantitative methods. Quantitative data is numerical data, data obtained from financial statements. Researchers use data collection techniques accompanied by documentation. The results showed that the efficiency ratio shows the turnover of fixed assets that are sold a lot so that the turnover of receivables increases so that profitability can increase profit growth So it was concluded that profit growth at PT. Makassar Industrial Estate (Persero) working capital management has not shown efficiency.